INDIKATOR JARAK AMAN MINIMUM MATA TERHADAPMONITOR MENGGUNAKAN SENSOR ULTRASONIK PING)))BERBASIS MIKROKONTROLER AT 89S51 - Tristianto dan Setiya Purnawan (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
This research aims at 1) designing an indicator device, 2) making anindicator device, 3) knowing the work of an indicator device of the safedistance of minimum visual range toward monitor using microcontroller AT89S51- based ultrasonic censor. It is hoped that this device can help the userof monitor in determining the safe distance of minimum visual range towardthe monitor. Thus, it can reduce the radiation risk.This research employed experimental-quantitative method, in whichthe researcher took part in the making and testing of the device. The basicconcept of the device design is stringing up some electronical componentswhich their works are interdependent in displaying the distance between theuser and the monitor. Starting from the distance detection, data processing,and data display, all will be assembled and work sinergically. The steps of thedevice making consist of two steps, they are the making of hardware andsoftware.Based on the steps of the program, it is found an indicator device ofminimum visual range toward monitor and a portable device. This device canhelp the user of monitor in determining the safe distance of minimum visualrange toward monitor.Key Word: indicator device, safe distance